Meaningful work and workplace democracy : a philosophy of work and a politics of meaningfulness - Yeoman, Ruth, 1964- (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2014)
"Meaningful Work and Workplace Democracy is a timely revival of the social and political importance of meaningful work. Drawing upon moral philosophy, political theory and sociology of work, this book creates a philosophy of work based upon the value of meaningfulness, and addresses contemporary concerns that work has become irretrievably degraded by evaluating how this understanding of meaningfulness remedies alienation, domination and distorted social recognition. In order to retrieve the emancipatory potential of all kind of work, this book argues for the institution of a new politics of meaningfulness through a system of workplace democracy which combines democratic authority with participatory practices, concluding that making work meaningful is both the legitimate and achievable object of political and social action"--
Machine generated contents note: -- Introduction1.Conceptualising Meaningful Work as a Fundamental Human Need2.Meaning-Making and an Ethic of Care3.Overcoming Alienation4.Confronting Domination5.Restoring Dignity6.'The Inner Workshop of Democracy'7.Capability Justice and a Politics of MeaningfulnessConclusion.
Keywords: Work environment -- Philosophy; HEALTH & FITNESS / Work-Related Health; PHILOSOPHY / Good & Evil; POLITICAL SCIENCE / Political Ideologies / Democracy; SOCIAL SCIENCE / Sociology / General; BUSINESS & ECONOMICS / Workplace Culture; PHILOSOPHY / Social